Natural Disaster Damage Indices Based on Remotely Sensed Data : An Application to Indonesia - Skoufias, Emmanuel; Strobl, Eric; Tveit, Thomas (World Bank, Washington, DC, 2017)
Combining nightlight data as a proxy for economic activity with remote sensing data typically used for natural hazard modeling, this paper constructs novel damage indices at the district level for Indonesia, for different disaster events such as floods, earthquakes, volcanic eruptions and the 2004 Christmas Tsunami. Ex ante, prior to the incidence of a disaster, district-level damage indices could be used to determine the size of the annual fiscal transfers from the central government to the subnational governments. Ex post, or after the incidence of a natural disaster, damage indices are useful for quickly assessing and estimating the damages caused and are especially useful for central and local governments, emergency services, and aid workers so that they can respond efficiently and deploy resources where they are most needed.